Targeting chaperone/co‐chaperone interactions with small molecules: A novel approach to tackle neurodegenerative diseases - Wang L.; Bergkvist L.; Kumar R.; Winblad B.; Pavlov P.F. (My University, 2025)
The dysfunction of the proteostasis network is a molecular hallmark of neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis. Molecular chaperones are a major component of the proteostasis network and maintain cellular homeostasis by folding client proteins, assisting with intracellular transport, and interfering with protein aggregation or degradation. Heat shock protein 70 kDa (Hsp70) and 90 kDa (Hsp90) are two of the most important chaperones whose functions are dependent on ATP hydrolysis and collaboration with their co‐chaperones. Numerous studies implicate Hsp70, Hsp90, and their co‐chaperones in neurodegenerative diseases. Targeting the specific protein–protein interactions between chaperones and their particular partner co‐chaperones with small molecules provides an opportunity to specifically modulate Hsp70 or Hsp90 function for neurodegenerative diseases. Here, we review the roles of co‐chaperones in Hsp70 or Hsp90 chaperone cycles, the impacts of cochaperones in neurodegenerative diseases, and the development of small molecules modulating chaperone/co‐chaperone interactions. We also provide a future perspective of drug development targeting chaperone/co‐chaperone interactions for neurodegenerative diseases. © 2021 by the author. Licensee MDPI, Basel, Switzerland.